A review on self-compacting concrete incorporating palm oil fuel ash as a cement replacement. (20th October 2020) - Adebayo Mujedu, Kasali; Ab-Kadir, Mariyana Aida; Ismail, Mohammad
Highlights: POFA, a waste material can be used to replace part of cement in the production of SCC. Heat treatment reduced the carbon content and LOI of POFA. SCC containing POFA showed high resistance against acid attack, sulfate attack. SCC incorporating POFA has high value of compressive strength at later days of curing. Ettringites were noticed in control SCC but it vanished for POFA SCC at 7 days. Abstract: Palm oil fuel ash (POFA) is a waste materials dumped into an open field of a palm oil industry and thus, caused environmental contamination and health threat problems. The problems can be lessened by making use of POFA as cement replacement materials. A lot of researchers have conducted a research to study the use of POFA as cement replacement in the production of normal and high strength self-compacting concrete (SCC). However, a strong review on the use of POFA to replace part of cement in the production of SCC is yet to be established. In this paper, physical, chemical properties, morphology of POFA, fresh, hardened and durability properties of SCC incorporating POFA were reviewed. The information presented has shown that sufficient data have been obtained from the review of different articles to give confidence in the general behavior of SCC incorporating POFA.